Review of pharmacological options for the treatment of Chagas disease - Lascano, María Fernanda (2020)
Chagas disease (CD) is a worldwide problem, with over 8 million people infected in both rural and urban areas. CD was first described over a century ago, but only two drugs are currently available for CD treatment: benznidazole (BZN) and nifurtimox (NF). Treating CD-infected patients, especially children and women of reproductive age, is vital in order to prevent long-term sequelae, such as heart and gastrointestinal dysfunction, but this aim is still far from being accomplished. Currently, the strongest data to support benefit–risk considerations come from trials in children. Treatment response biomarkers need further development as serology is being questioned as the best method to assess treatment response. This article is a narrative review on the pharmacology of drugs for CD, particularly BZN and NF. Data on drug biopharmaceutical characteristics, safety and efficacy of both drugs are summarized from a clinical perspective. Current data on alternative compounds under evaluation for CD treatment, and new possible treatment response biomarkers are also discussed. Early diagnosis and treatment of CD, especially in paediatric patients, is vital for an effective and safe use of the available drugs (i.e. BZN and NF). New biomarkers for CD are urgently needed for the diagnosis and evaluation of treatment efficacy, and to guide efforts from academia and pharmaceutical companies to accelerate the process of new drug development.